2020
DOI: 10.1038/s41419-020-02934-8
|View full text |Cite
|
Sign up to set email alerts
|

Combined inhibition of JAK1/2 and DNMT1 by newly identified small-molecule compounds synergistically suppresses the survival and proliferation of cervical cancer cells

Abstract: Despite substantial advances in treating cervical cancer (CC) with surgery, radiation and chemotherapy, patients with advanced CC still have poor prognosis and significantly variable clinical outcomes due to tumor recurrence and metastasis. Therefore, to develop more efficacious and specific treatments for CC remains an unmet clinical need. In this study, by virtual screening the SPECS database, we identified multiple novel JAK inhibitor candidates and validated their antitumor drug efficacies that were partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 56 publications
(61 reference statements)
0
18
0
Order By: Relevance
“…Thus, finding other therapeutic strategies to curb ICI-induced musculoskeletal inflammation and maintain antitumor activity will be required to meet current clinical needs in the management of ICI-irAEs. Preclinical studies on human cancer cell lines have shown that JAK-pathway inhibition impairs tumor growth [35,36]. Still, new data on increased risk of malignancy in RA patients associated with Tofacitinib use put the previously favourable assessment of JAKi in vitro and in vivo into question [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, finding other therapeutic strategies to curb ICI-induced musculoskeletal inflammation and maintain antitumor activity will be required to meet current clinical needs in the management of ICI-irAEs. Preclinical studies on human cancer cell lines have shown that JAK-pathway inhibition impairs tumor growth [35,36]. Still, new data on increased risk of malignancy in RA patients associated with Tofacitinib use put the previously favourable assessment of JAKi in vitro and in vivo into question [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Moreover, we found that DNMT1 rs16999593 was more common in patients with TNM stage 0-II, no lymph-node metastasis and negative expression of HER2, which indicates that DNMT1 could regulate gene expression in an epigenetic manner, resulting in the pathological characteristics of cancers. [36][37][38] Functionally, rs16999593, a missense variant, changes from T to C in amino acid 97 (histidine to arginine), which may disrupt the function of DNMT1, thereby increasing the susceptibility to cancer; 35 however, the function of substitution caused by the polymorphism is still unclear. In addition, our results showed that DNMT1 rs2228611 was a protective risk factor for BC patients.…”
Section: Discussionmentioning
confidence: 99%
“…SGI-1027 may inhibit DNMT activity, induce the degradation of DNMT1 and reactivate tumor suppressor genes [ 69 ]. SGI-1027 can also impair cervical cancer cell and hepatocellular carcinoma cell propagation by dramatically increasing apoptotic cell death and cell cycle arrest [ 69 , 70 ]. As a novel DNMT inhibitor, MC3343 is more potent and selective than SGI-1027 toward other S-adenosylhomocysteine-dependent (SAM-dependent) methyltransferases [ 71 , 72 ].…”
Section: Dna Hypomethylating Drugs and Their Clinical Application In Solid Tumorsmentioning
confidence: 99%